ZONED CALC-ALKALINE PLUTONS IN NORTHEASTERN KAMCHATKA, RUSSIA: IMPLICATIONS FOR THE CRUSTAL GROWTH IN MAGMATIC ARCS - Kepezhinskas P.K.; Reuber I.; Tanaka H.; Miyashita S. (My University, 1993)
The Upper Cretaceous oceanic and island-arc terranes of Northeastern Kamchatka (Russia) are intruded by numerous ultramafic and mafic to intermediate plutons. Ultramafic plutons north of Epilchik Lake show a concentric structure: dunites in the core pass progressively outwards into wehrlites and pyroxenites and into gabbros along the rim which are occasionally phlogopite- and amphibole-bearing. Compositional layering and mineral orientations marked by spinel clusters in the dunites and by acicular amphiboles in the marginal gabbros are parallel to the contacts. The mafic to intermediate plutons studied in the Machevna area show similar concentric structure with a dioritic core and a gabbroic rim. Magmatic flow lines are near-vertical in the central part of the plutons. These internal structures and general geometry of the plutons suggest vertical magma intrusion into mega-tension gashes developed initially at a high angle to the subduction zone. Olivine, pyroxenes, and plagioclase have primitive compositions. Al-rich, highpressure amphiboles are followed by Al-poor, low-pressure hornblendes. A two stage model of pluton crystallization and emplacement is proposed: initial crystallization and seggregation at the Moho level below the intraoceanic island are (approximately 22–25 km depth) and final emplacement followed by partial recycling of primary ultramafic cumulates and solidification at upper crustal levels (approximately 8–10 km depth). Emplacement of the arc plutons was accompanied by epidote amphibolite-facies contact metamorphism of host volcanic and pyroclastic rocks. Major- and trace-element analyses of plutonic rocks indicate calc-alkaline affinities and emplacement in a primitive arc setting. The tectonic setting, age, and emplacement structures suggest that these plutons mark the change of geodynamic conditions from arc-related compression to local extension probably related to the initial stages of opening of the proto-Komandorsky basin. A two stage model for the crustal growth in magmatic arcs is proposed based on northeastern Kamchatka plutons. During stage I, primitive basaltic melts were emplaced along the crust-mantle boundary below the arc. Continuous fractionation and accumulation of olivine-rich cumulate rocks at the base of the growing island-arc crust resulted in production of evolved melt which was further emplaced in the upper arc crust. Crystal fractionation of a shallow, stage II magmatic reservoir below the active arc volcanoes resulted in formation of a significant amount of plutonic rocks and eruption of mafic to intermediate calc-alkaline lavas at the surface.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая